Redescriptions of ten chigger mite species (Acariformes: Trombiculidae) from Vietnam - Antonovskaia, Anastasia A.; Stekolnikov, Alexandr A. (Zootaxa, 2021)
Ten species of chigger mites from the genera Gahrliepia Oudemans, 1912, Walchia Ewing, 1931, Cheladonta Lipovsky, Crossley and Loomis, 1955, Doloisia Oudemans, 1910, Schoutedenichia Jadin and Vercammen-Grandjean, 1954, and Microtrombicula Ewing, 1950, incompletely described by Schluger et al. (1960a, c, 1961, 1963) from rodents in North Vietnam, are redescribed based on type series. Lectotypes and paralectotypes have been designated for all species. A new synonymy has been established: Walchia delicatula (Schluger, Grochovskaja, Ngu, Hoe and Tung, 1960) (= Walchia tianguangshanensis Zhao, 1981 syn. nov.).